O mundo dos mortos no quotidiano dos vivos: celebrar a morte nas Misericórdias portuguesas da época moderna - Araújo, Maria Marta Lobo de (2010)
Our work analyzes death in the Portuguese Misericordias of the modern age, highlighting the role played by death in living daily life. We studied mortuary practices and the mechanisms triggered by these institutions to attain salvation, showing the weight of death in the kingdom of the living.